Classification of graphic designers' competencies using discriminant analysis - Umam, Khairul; Duskri, Muhammad; Idris, Khairiani; Akmal, Nurul; Hidayat, Mukhlis (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
Graphic design is a field that operates in various sectors such as advertising, media, global marketing, and entertainment. Graphic designers have a central role in creating artworks that are both aesthetically pleasing and effective in conveying messages to audiences. The purpose of this study is to classify graphic designer competencies into beginner, intermediate, and advanced categories. This research employs a quantitative descriptive approach. The population of this study is graphic designers in Banda Aceh. The research sample was determined using purposive sampling, with a minimum work experience of one year. Research data were collected through observation and tests. The data analyzed using discriminant analysis with the aid of SPSS. Discriminant analysis producted a discriminant fungction that was used to predict the competency level group of graphic designers more objectively based on influencing factors (variables) such as creativity, attention to detail, visual ability, and technical ability. Based on classification results using the discriminant function, it was determined that 33 designers were classified as beginners, 27 as intermediate, and 28 as advanced. The prediction accuracy of the discriminant function in classifying data correctly was 75%. The discriminant function can be effectively employed as a tool for selecting or evaluating the competencies of graphic designers.